Pemetaan Komoditas Hortikultura Sebsektor Sayur-sayuran di Provinsi Sumatra Barat - Azmi, Azmi; Hadiguna, Rika Ampuh; Jonrinaldi, Jonrinaldi (JURNAL AGRICA, 2025)
This study aims to map the most potential vegetables to be developed in West Sumatra Province.The Location Quotient (LQ) method is employed to identify leading and non-leading commodities,while the Shift Share Analysis (SSA) is used to analyze structural changes and the competitivenessof the commodities. The study utilizes secondary data in the form of vegetable sub-sectorhorticultural production data by regency/city over a six-year period (2017–2022). The results showthat large chili is the leading vegetable commodity in West Sumatra, with an LQ value greater than1 across 17 regencies/cities. Conversely, garlic is categorized as a non-leading commodity, with anLQ > 1 found in only one regency. Nevertheless, garlic is identified as the most progressivecommodity based on the highest net shift value. Net growth of vegetable sub-sector commoditieswas identified in 10 out of 18 regencies/cities, with Solok Regency contributing the most. In termsof individual commodities, cabbage recorded the highest net growth, while chayote experienced thelowest. The resulting commodity mapping can serve as a basis for local government in formulatingspatial and sustainable development policies, as well as a strategic reference for businesses andinvestors in directing horticultural investments in West Sumatra.